CONCERN FOR THE ENVIRONMENT: THE ROLE OF THE ENVIRONMENT IN ORGANIZATIONAL SUSTAINABILITY - Dodi Setiawan Riatmaja; Ernes Septina Azizi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
The environment plays a vital role in the sustainability of an organization, both as a primary resource provider and as a strategic element that influences the operational stability and reputation of an organization. This study aims to examine the relationship between environmental awareness and organizational sustainability, with a focus on the role of the environment as a key supporting element in resource management, regulatory compliance, and value-added creation. The method used in this study is a literature review, in which various sources such as scientific journals, books, and organizational reports are analyzed to gain an in-depth understanding of effective sustainability practices. The results of the study indicate that organizations that care about the environment tend to be better able to face global challenges, such as climate change, resource scarcity, and social pressure from consumers who are increasingly aware of sustainability issues. In addition, environmental awareness strategies, such as resource efficiency, environmentally friendly product innovation, and collaboration with stakeholders, not only support environmental conservation but also increase the competitiveness and reputation of the organization in the market. Thus, environmental awareness is not only a moral obligation, but also an important strategic investment for the sustainability of the organization in the future.